2009
DOI: 10.2967/jnumed.109.066639
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 68Ga-DOTATATE and 18F-FDG PET/CT in Pulmonary Neuroendocrine Tumors

Abstract: Our purpose was to compare the performance of 68 4,7,N9,N$,N%-tetraacetic acid-D-Phe 1 , Tyr 3 -octreotate (DOTATATE), a novel selective somatostatin receptor 2 PET ligand, and 18 F-FDG in the detection of pulmonary neuroendocrine tumors using PET/CT, with correlation of uptake and tumor grade on histology. Methods: The imaging findings of the first 18 consecutive patients (8 men and 10 women) with pulmonary neuroendocrine tumors (11 typical carcinoids, 2 atypical carcinoids, 1 large cell neuroendocrine tumor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
136
4
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(157 citation statements)
references
References 20 publications
(41 reference statements)
12
136
4
5
Order By: Relevance
“…Some papers report limited value of 18-FDG PET CT in detecting neuroendocrine tumours, due to low proliferative activity of these tumours. 11,12 However this examination was positive in our case, in accordance with the findings of Daniels et al who demonstrated a trend toward higher PET sensitivity for atypical carcinoid tumors in their cohort. 13 A multidisciplinary approach is required in order to diagnose and localise ACTH oversecretion.…”
Section: Discussionsupporting
confidence: 82%
“…Some papers report limited value of 18-FDG PET CT in detecting neuroendocrine tumours, due to low proliferative activity of these tumours. 11,12 However this examination was positive in our case, in accordance with the findings of Daniels et al who demonstrated a trend toward higher PET sensitivity for atypical carcinoid tumors in their cohort. 13 A multidisciplinary approach is required in order to diagnose and localise ACTH oversecretion.…”
Section: Discussionsupporting
confidence: 82%
“…Studies have demonstrated that de-differentiated neuroendocrine tumours (NET) exhibit high GLUT-1 glucose transporter expression with low expression of somatostatin receptor [35,36]. This gives the notion that somatostatin receptor expression lesions are generally associated with differentiated tumours, and as these tumours transform to more aggressive behaviour, there is shift from 68 Ga-DOTA-peptide uptake to 18 F-FDG uptake-the so called 'flip-flop' phenomenon.…”
Section: F-fdg Pet/ct Images Although 68mentioning
confidence: 99%
“…These authors demonstrated that typical BCs showed significantly higher uptake of 68 Ga-somatostatin analogues and significantly lower uptake of 18 F-FDG compared to pulmonary NETs of higher grade. No false-positive uptake of 68 Ga-DOTATATE was reported in this study population, but there were three sites of false-positive uptake of 18 F-FDG due to inflammation [12]. Jindal et al retrospectively evaluated the role of 68 Ga-DOTATOC and 18 F-FDG PET/CT in differentiating typical and atypical BCs.…”
mentioning
confidence: 66%
“…Furthermore, 68 Ga-somatostatin analogues provided better results compared to the radiolabelled amino acid 18 Fdihydroxyphenylalanine (DOPA) in evaluating lung NETs [6], but literature reports specifically addressing the use of 18 F-DOPA in pulmonary NETs are few [11]. Since different information may be obtained using various PET tracers, some authors have recently reported preliminary results on dual-tracer PET/CT imaging using 68 Ga-somatostatin analogues and 18 F-FDG in well-differentiated pulmonary NETs [12][13][14][15]. A retrospective study by Kayani et al compared 68 Ga-DOTATATE and 18 F-FDG PET/CT findings in 18 patients with pulmonary NETs, including 13 BCs.…”
mentioning
confidence: 99%